LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK PROBLEM SOLVING UNTUK MENCEGAH PERILAKU AGRESIF PESERTA DIDIK KELAS VIII DI SMP KP CIPARAY - Nadia, Nadia Zakiah Maharani; Sobari , Teti; Renata Manuardi, Ardian (IKIP Siliwangi, 2025)
This research aims to determine whether problem solving techniques can reduce students' aggressive This research aims to find out whether problem solving techniques can reduce students' aggressive behavior in group guidance services. Aggressive behavior is behavior that aims to injure or destroy. The research was located at Karya Pembangunan Ciparay Middle School. The research method used is a Mix method with a Sequential Exploratory design. The student subjects were selected using a non-probability sampling technique with a purposive sampling type, namely with the criteria of class VIII students and a high/moderate aggressive behavior scale, totaling 6 students. Data collection is through non-test instruments in the form of interviews and observations, and test instruments in the form of questionnaires. The research results can be seen from the t-test calculation carried out with the help of SPSS 23.0 which states that the average before service was 94.83 and after service 50.83 which shows a significant decrease, while the sig (2-tailed) value is 0.000 or < 0.05 so it can be concluded that problem solving techniques have a significant relationship to reducing aggressive behavior in students.